Osteosarcoma of the Mandible Masquerading as a Dental Abscess: Report of a Case - Sukumaran Anil; Anitha P. Krishnan; R. Rajendran (Case Reports in Dentistry)
An aggressive and fatal case of osteosarcoma of the mandible in a 19-year-old female is reported. Six weeks after the clinical appearance of the swelling, the patient died. This paper is unique in that the age of occurrence and the biologic behavior of the tumor were not consistent with the reported literature. The case report is followed by a brief review of osteosarcoma of the jaw with a note on its clinical presentation, diverse radiologic appearance, varied histopathologic picture, and prognosis.